Study of the affine function and applications in the areas of mathematics and physics with an emphasis on contextualized teaching (International Seven Journal of Multidisciplinary, 2023)
This work deals with a study of the affine function or polynomial function of the first degree, emphasizing some applications in the areas of Mathematics and Physics with an emphasis on everyday life. Firstly, it tells how some important researchers gave theoretical impetus for the study of the affine function to become consistent. Therefore, with the development of this subject, it became possible to solve a series of everyday problems, such as in the commercial area, in mathematics itself and in the study of kinematics in movements of bodies that are governed by constant and non-zero velocities. This function has also been applied to tariffs, such as company plans, the cost per minute of cell phone calls, cab fares, etc. Therefore, the study of the affine function has a large number of practical applications and the teacher, when teaching the content, should promote a methodology that is linked to the theoretical-practical part so that the student is able to realize the relevance that the affine function assumes in the context of everyday life. This concludes the research by showing the viability of the teacher articulating in the classroom, considering a study that is linked to the classroom and the student's daily life where they are able to understand the interaction between the two processes of teaching and learning with problems that clarify and give more meaning to the content taught theoretically.